Politics and Policy in Australia’s States and Territories
XIV, 398 p. 17 illus., 13 illus. in color.
Keywords: This book offers the first critical examination of Australian State and Territory politics in over 20 years. It presents a major updating of the field, with deep analysis of key political, electoral and policy developments in all the States and both Territories over the last decade. The volume addresses a substantial gap in our understanding of politics and policy in Australia, providing systematic scholarly analysis of many new developments, including major policy reforms, and the rise of long-serving and important political leaders, such as Dan Andrews in Victoria and Anna Palaszczcuk in Queensland. In Part One, the authors offer new comparative and thematic analyses of State and Territory politics, including electoral innovations; Commonwealth–State relations; historical context; and gender policy and politics. In Part Two, contributors provide an analytical overview of politics in the past decade in each jurisdiction. The final chapter includes a comparative survey, focusing on electoral trends, policy developments and ideological changes. The book will appeal to scholars of Australian politics across a range of dimensions, from electoral politics to federal dynamics and specific policy concerns, and, more widely, to any reader interested in the politics of Australia. The book is an ideal teaching resource and suited to be integrated as recommended or supplementary reading in a wider range of university undergraduate and postgraduate courses on Australian politics and policy. James C. Murphy is Lecturer in Australian Politics at the University of Melbourne, Australia. He studies Victorian State politics and policy conflict in Australia, and published his first book The Making and Unmaking of East–West Link, based on his PhD thesis in 2022. Jim teaches politics, public policy and electioneering. Alan Fenna is Professor of Politics at the John Curtin Institute of Public Policy, Curtin University, Western Australia. He publishes widely on public policy and Australian and comparative federalism and served as President of the Australian Political Studies Association (APSA) 2009–10. Rob Manwaring is Associate Professor in the College of Business, Government and Law, Flinders University, Australia. He teaches a range of policy and politics topics, and researches into the areas of centre–left political parties, democratic politics, and public policy. Rob is a former President of the Australian Political Studies Association (2023–24), and was a co-editor for the Australian Journal of Political Science (2022–24).